The effects of solar radiation on daily and seasonal stem increment of canopy trees in European temperate old-growth forests - Kašpar, Jakub; Krůček, Martin; Král, Kamil (The New phytologist, 2024)
It is well established that solar irradiance greatly influences tree metabolism and growth through photosynthesis, but its effects acting through individual climate metrics have not yet been well quantified. Understanding these effects is crucial for assessing the impacts of climate change on forest ecosystems. To describe the effects of solar irradiance on tree growth, we installed 110 automatic dendrometers in two old-growth mountain forest reserves in Central Europe, performed detailed terrestrial and aerial laser scanning to obtain precise tree profiles, and used these to simulate the sum of solar irradiance received by each tree on a daily basis. Generalized linear mixed-effect models were applied to simulate the probability of growth and the growth intensity over seven growing seasons. Our results demonstrated various contrasting effects of solar irradiance on the growth of canopy trees. On the one hand, the highest daily growth rates corresponded with the highest solar irradiance potentials (i.e. the longest photoperiod). Intense solar irradiance significantly decreased tree growth, through an increase in the vapor pressure deficit. These effects were consistent for all species but had different magnitude. Tree growth is the most effective on long rainy/cloudy days with low solar irradiance.
Keywords: Photosynthesis; Trees; Fagus sylvatica; climate‐growth limitation; dendrometer; Forests; lesy; stromy; Europe; sluneční záření; solar irradiance; roční období; Seasons; Picea abies; Abies alba; Plant Stems; Sunlight; tree growth; fotosyntéza; stonky rostlin; Evropa